Determinants of intention and acceptance of halal vaccine and pharmaceutical drugs: the roles of knowledge, attitudes, and behavior - Etin Diah Permanasari; Careninda Ayu Bella; Imawati Eka Putri (Jurnal Konseling dan Pendidikan, 2025)
Halal awareness leads a key role in shaping health-related decision making among Muslim. As Muslims are obliged to consume halal products, concerns regarding halal status may influence their intention to accept vaccines and pharmaceutical drugs. The study aim is to assess the acceptance of halal vaccines and drugs based on the level of halal awareness among DKI Jakarta residents by halal knowledge, attitudes, and behavior. This cross-sectional was conducted among 400 respondents. Data were analyzed using univariate and bivariate analyses, with Spearman’s rho employed to assess correlations between variables. The results showed that the level of knowledge was moderate (59.5%), for attitude was categorized as positive (84.5%), and behavior was low (44.5%). As for the correlation results with the Spearman rho test, it was concluded that there was a relationship between the level of knowledge and attitude, the result was a p-value of 0.016 (P<0.05) from a negative value of r= -0.121, while between the level of knowledge and behavior the relationship was a p-value of 0.001 (P<0.05 ) from a value of r = 0.289, and between attitudes and behavior there is a relationship as the variable value showed of p-value 0.036 (P<0.05) from a negative value of r = -0.105. These findings indicate that halal awareness significantly influences intention and acceptance behavior toward halal vaccines and drugs.